Identificação de alterações moleculares associadas à expressão de CD133, CXCR4, CD44 E OLIG2 e metilação em promotor de CDKN2A em tumores astrocíticos - Alves, Markênia Kélia Santos (2014)
Currently, the concept that tumors are cell populations organized in a hierarchically heterogenous way in which stem-cells are relevantly important as these cells have the capacity of self-renew and of generating cell lineages in different phases of differentiation. So that, the identification of stem-cell components is essential to tumorigenesis understanding. Althought neural cell lineage markers have been identified, the association among these markers and neurological tumors is still scarce, and taking in consideration the astrocytomas, the association assessements are verified mainly regarding the glioblastomas. Among these stem cell markers, CD133, CXCR4 and CD44 are related to the glioma formation, migration and growth; on the other hand, OLIG2 is involved in cell destination. So far there are no studies evaluating all these markers together and their relationship to tumor grades. Additionally, specific epigenetic alterations, specially promoter methylation, have been widelly identified in these tumors, leading to gene inativation, mostly involving CDKN2A (p16INK4A protein), a tumor suppressor. Althought this mechanism is pointed as this gene main inactivator, there are still controvertial questions regarding the astrocytomas. In order to evaluate these questions, the present study aimed to determine CDKN2A pattern of methylation and expression and their association to clinicalpathological parameters, and if the presence of progenitor/stem-cells, taking CD133, CXCR4, CD44 and OLIG2 expression in consideration, could define subpopulations of cells which might be used as prognostic markers. So, in a series of 93 astrocytomas of different malignity grades, the expression of CD133, CXCR4, CD44, OLIG2 and p16INK4A was analysed by the imunohistochemistry technique, and the CDKN2A methylation status was assessed by methylation specific PCR (MS-PCR). The data was then associated to tumor grades, localization and other clinicalpathological parameters. The statistic analyses were made using X 2 test, Fisher's exact test, Spearman's correlation, kmeans groupment and principal component analyses, using p<0.05 as statistically significance. The imunopositivity of OLIG2 was predominant (73.1%), followed by CXCR4 (60.2%), CD44 (55.9%) and CD133 (45.2%). The correlation and groupment analyses defined two different population subtypes, a CXCR4(+)CD133(+)CD44(+) subtype and a OLIG2(+) subtype. CXCR4(+)CD133(+)CD44(+) tumors became more frequent as malignity grew. In grade IV, this subtype was significantly more frequent (p=0.008), being also in diffuse tumors. Additionally, CXCR4(+) and CD133(+) tumors were preferentially located in brain hemisferes and in the ventricles, and mostly in aged >30 patients. On the other side, OLIG2(+) tumors were associated to the cerebellum, which is the pylocitic tumor preferential localization. A strong negative correlation between nuclear and cytoplasmatic imunopositivity and promoter methylation in CDKN2A was observed. Also, a negative significant correlation between methylated CDKN2A and patient's age was found; moreover, feminine patients presented a higher frequency of methylated CDKN2A. In conclusion, the presence of stemcell subpopulations in astrocytomas indicates tumoral progression, in which CXCR4, CD133 and CD44 may be potentially used together as prognostic markers. The association between tumor localization and patient's age also corroborates these findings. Additionally, the CDKN2A inactivation by promoter methylation is a frequent event in astrocytomas and it is associated to patient's age and gender.